2021
DOI: 10.1186/s40560-021-00536-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymphocyte counts in bronchoalveolar lavage fluid in patients with acute respiratory failure: a retrospective cohort study

Abstract: Background Cellular patterns in bronchoalveolar lavage fluid (BALF) are used to distinguish or rule out particular diseases in patients with acute respiratory failure (ARF). However, whether BALF cellular patterns can predict mortality or not is unknown. We test the hypothesis that BALF cellular patterns have predictive value for mortality in patients with ARF. Methods This was a retrospective single-center observational study conducted in a Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…These diseases are usually responsive to glucocorticoids and administration of glucocorticoids was recommended [21]. Additionally, a high lymphocytes percentage in BALF was correlated with good prognosis in interstitial pneumonia or acute respiratory failure in the studies that most of cases had been administered glucocorticoids [22,23]. We speculate that enriched lymphocytes in BALF is associated with good responsiveness to glucocorticoids and, as a result, with good prognosis in DAH.…”
Section: Discussionmentioning
confidence: 82%
“…These diseases are usually responsive to glucocorticoids and administration of glucocorticoids was recommended [21]. Additionally, a high lymphocytes percentage in BALF was correlated with good prognosis in interstitial pneumonia or acute respiratory failure in the studies that most of cases had been administered glucocorticoids [22,23]. We speculate that enriched lymphocytes in BALF is associated with good responsiveness to glucocorticoids and, as a result, with good prognosis in DAH.…”
Section: Discussionmentioning
confidence: 82%
“…Patients with BALF lymphocytes ≥ 20% had significantly higher 1-year survival compared to patients with BALF lymphocytes< 20% [52] . In studies related to acute exacerbations of chronic progressive interstitial pneumonia, mortality was significantly lower in patients with BALF lymphocytes ≥ 15% compared to those with BALF lymphocytes< 15% [53] . In addition, a BALF total leukocyte count ≥ 510/µL was considered an independent predictor of bacterial pneumonia [54] .…”
Section: Discussionmentioning
confidence: 87%
“…Hirasawa et al. reported that BALF-lymphocyte percentage ≥20% was significantly associated with increased 90-day and 1-year survival in patients with acute respiratory failure (ARF) caused by interstitial lung disease or non-interstitial lung disease ( Hirasawa et al., 2021 ). These findings suggested that BALF-lymphocytes may play a vital role in the prognosis of PCP patients with RF, and the usefulness of BALF-lymphocytes warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%